STRATEGI PEMASARAN DALAM PENGEMBANGAN DESA WISATA SIDATAPA KECAMATAN BANJAR KABUPATEN BULELENG - A. A. Istri Agung Maheswari; A. A. Ngr. Oka Suryadinatha G; Ni Putu Yunita Anggreswari; Nyoman Sri Manik Parasari; Ni Nyoman Sri Wisudawati (LPSDI Bina Patria, 2023)
Tourism village is a form of combination of accommodation, attractions, supporting facilities that are presented in the pattern and structure of community life that blends with culture, nature, art and traditions that apply to the community. With the existence of this tourism village, it is expected to be able to grow and develop into the management of a tourism business sector, and requires the right marketing strategy. One of the villages that has tourism potential to be developed is Sidatapa Village. Sidatapa Village, known as Baliaga Village, has natural beauty, very unique regional arts and ancestral cultural heritage in the form of traditional houses that must be preserved. However, in its development there are still obstacles, especially in terms of promotion and marketing. To be able to survive and thrive in the tourism industry, a marketing strategy is needed by the destination manager. Data collection was carried out through observation, literature study and interviews with village officials and environmental awareness leader group who are responsible for tourism in Sidatapa Village. Strategy analysis is done by using SWOT analysis. Based on the results of the analysis, it was found that there needs to be a promotion strategy and increase cooperation, re-branding image of tourist destinations, forming a professional team and preparing tour package rates, as well as further optimizing tourism products and the performance of tourism destination managers in Sidatapa Village